Study of the influence of the quality of the feedstock on the process of catalytic oxidation of SO₂ to SO₃ in a contact apparatus for the production of sulfuric acid - Nosalskyi, Dmytro Vladyslavovych; Deinekа, Dmytro Mykolayovych; Vetsner, Yulana Igorivna; Mykhailova, Evgenia Oleksandrivna; Kobziev, Oleksandr Viktorovych (Національний технічний університет "Харківський політехнічний інститут", 2025)
In the modern sulfuric acid industry, vanadium catalysts play an important role in the oxidation of sulfur dioxide (SO2) to sulfur trioxide (SO3). However, the efficiency of these catalysts can be significantly reduced by the presence of impurities such as calcium and iron. In this article, we will consider the effect of these impurities on the operation of the first layer of vanadium catalyst and try to identify the optimal conditions for ensuring stable operation of the process, starting from the feedstock and ending with the compounds formed as a result of combustion in furnaces. Special attention is paid to the requirements for the feedstock, because they can significantly affect first the heat transfer, and then the activity of the catalyst and its hydraulic resistance. It has been shown that factors such as the origin of sulfur, the method of its transportation and the combustion temperature can be the main sources of calcium impurities, while the temperature of the sulfur combustion process, corrosion products of metal parts of the furnace and boiler recycler are the main sources of iron impurities. In addition, attention should be paid to the influence of the physicochemical properties of the starting material on the process of formation of calcium and iron compounds. It is important to consider not only the composition of the raw material, but also the conditions of its extraction, transportation and storage, since this can significantly affect the quality of the final product and the efficiency of the production process. У сучасній промисловості виробництва сірчаної кислоти важливу роль відіграють ванадієві каталізатори, що використовуються для окислення сірки діоксиду (SO₂) до триокису сірки (SO₃). Однак, ефективність роботи цих каталізаторів може значно знижуватися через наявність домішок, таких як кальцій та залізо. У цій статті ми розглянемо вплив цих домішок на експлуатацію першого шару каталізатора ванадієвого і постараємося виявити оптимальні умови для забезпечення стабільної роботи процесу, починаючи з вихідної сировини і закінчуючи сполуками, що утворюються в результаті горіння в печах. Особлива увага приділяється вимогам до вихідної сировини, тому що вони можуть суттєво впливати спочатку на тепловіддачу, а потім активність каталізатора та його гідравлічний опір. Було показано, що такі фактори, як походження сірки, спосіб її транспортування та температура горіння можуть бути основними джерелами утворення кальцієвих домішок, в той час як температура процесу спалювання сірки, продукти корозії металевих деталей печі та утилізатора котла є основними джерелами утворення залізних домішок. Крім того, слід звернути увагу на вплив фізико-хімічних властивостей вихідної сировини на процес утворення сполук кальцію та заліза.
Дослідження впливу якості вихідної сировини на процес каталітичного окислення SO₂ до SO₃ в контактному апараті для виробництва сірчаної кислоти
Keywords: vanadium catalyst; combustion; sulfur; sulfuric acid; mpurities; calcium compounds; iron compounds; ванадієвий каталізатор; горіння; сірка; сульфатна кислота; домішки; сполуки кальцію; сполуки заліза